DUTY IN THE SYSTEM OF MANDATORY PAYMENTS - Вишновецький, Вадим Михайлович (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2009)
The article deals with the place of duty in the system of obligatory payments. After analyzing different approaches to the solution of this issue, the author concludes that the duty is an independent form of compulsory payments, which occupies an intermediate link between taxes and fees.